O Bodhisattva Ascético: sua iconografia no contexto do desenvolvimento da tradição budista Mahayana em Gandhara - Piccin, Estela (2021)
Ascetic practices are common in Indian religions, and Śākyamuni Buddha once practiced forms of extreme asceticism before attaining Complete Enlightenment. Statues that represent this period of asceticism emerged in Gandhāra, the same region where the Indian culture and the Hellenism met, and where one of the main branches of Buddhism developed: the Mahāyāna tradition. In this research we will seek to understand the religious language of the image of the Bodhisattva Ascetic within the Buddhist Iconography of Gandhāra and relate the religious and philosophic values represented by it within the Early Mahāyāna. To this end, we intend to answer the following questions: What are the meanings of the image of the Ascetic Bodhisattva in its context of emergence at the time of the Early Mahāyāna tradition? What are the compositional characteristics and main motifs of the images of Ascetic Bodhisattvas? Which religious and philosophic conceptions of the Early Mahāyāna tradition of Gandhāra are behind the image of the Ascetic Bodhisattva? The methodology will be the Iconology of Erwin Panofsky, as well as the concepts of Nachleben and Pathosformel of Aby Warburg, with the aid of the mapping of visual modalities by Gillian Rose. This project is part of the Post-Graduation Program in Religious Studies at UMESP, from the Area of Concentration of Languages of Religion within the Research Line of Theologies of Religions and Culture.